The Globalization of an Interaction Ritual Chain: "Clapping for Carers" During the Conflict Against COVID-19. (22nd October 2021) - Rigal, Alexandre; Joseph-Goteiner, David
Abstract: Sociologists have long been interested in the theoretical possibility of a universal ritual. Despite a growing number of indicators of world society and globalization, there have not been attempts to observe and analyze the international reach of particular rituals. We propose an extension of the "interaction ritual chain" by theorizing how an interaction ritual might be created and diffused internationally. We look at the case of the COVID-19 pandemic, which created shared conditions of social distancing and emotional distress. We analyze a discontinuous chain of urban and national interaction rituals that focused attention on the efforts of healthcare workers fighting the virus. We count clapping and noise-making in 101 countries and 26 global cities. While we find similar ritual forms and international symbols of solidarity, there was also substantial evidence of conflict and particularism.